PENERAPAN PEMBELAJARAN SENTRA BAHAN ALAM TERHADAP PERKEMBANGAN KREATIVITAS ANAK USIA 5-6 TAHUN DI SEKOLAH ALAM PALEMBANG - Vyanti, Ades; Cindrya, Elsa; Imtihana, Aida (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research is entitled The Application of Natural Material Center Learning to the Development of Creativity of 5-6 Year Old Children at Sekolah Alam Palembang. The problem in this study is the application of natural material center learning to the development of creativity of children aged 5-6 years at Sekolah Alam Palembang. This study aims to analyze the application of natural material center learning and its impact on the development of creativity of children aged 5-6 years at Sekolah Alam Palembang. The research used a case study approach with five subjects of group B children. Data collection techniques were carried out through observation, interviews, and documentation. The results show that the natural materials center approach is able to optimize aspects of children's creativity such as imagination, interest in creative activities, and the ability to express themselves. In addition, this approach also contributes to children's social-emotional, cognitive, and motor development. The main obstacles found were limited teaching materials and time. This study suggests training teachers in the use of local materials and strengthening the program through seminars or webinars.